(untitled) (CIPEEX, 2025)
Ligaments play a crucial role in the passive stabilization of joints. Instability leads to decreased quality of life, reduced activity levels, and the management of patients with ACL injury may involve either surgical or non-surgical treatment. The aim of this study was to analyze the epidemiological profile of patients with anterior cruciate ligament (ACL) rupture, identifying the main injury mechanisms and associated risk factors. This was a descriptive, cross-sectional, and quantitative study conducted at a referral orthopedic hospital in north-central Goiás, designed to identify patterns and correlations between different risk factors and the occurrence of ACL injuries. Data were collected through a sociodemographic questionnaire prepared by the authors. A total of 27 individuals with ACL rupture were evaluated: 22.2% were female and 77.8% were male, with a mean age of 34 years. Injuries were caused mainly by sports activities (48.1%), followed by falls (18.5%), animal-related accidents (14.8%), motorcycle accidents (7.4%), and work-related accidents, representing only 3.7% of cases. Therefore, it can be concluded that males are more prone to ACL rupture, particularly in active and productive age groups, and that injury mechanisms are determining factors in its occurrence, with sports-related activities being the most prevalent. Preventive measures should be adopted to reduce the high rate of such injuries, aiming to promote greater well-being and contribute to public health.